Factors associated with delay in diagnosis among tuberculosis patients in the north of Iran (Medical Journal of Indonesia, 2021)
BACKGROUND Recognizing factors that affect delay in diagnosis in patients with pulmonary tuberculosis (TB) is critical. This study aimed to identify such factors among TB patients in the north of Iran. METHODS In this retrospective cohort study, we reviewed patient’s medical records from the TB registration system of the Health Deputy of Mazandaran University of Medical Sciences, Sari, Iran that was responsible for the TB registry in the province from 2007 to 2017. All hospitals affiliated with the university, including private hospitals, reported TB cases directly to the health deputy. Patient’s gender, age, TB smear result, TB type, imprisonment, diabetes, nationality, residence area, and drug use were considered factors of delay in diagnosis, which was defined as a delay of >30 days between symptom onset and diagnosis. Data from 3,453 patients were analyzed using the chi-square test and logistic regression models. RESULTS The frequency of patients with delay in diagnosis was 67.7%. There was no association between delay in diagnosis and gender (p = 0.194), TB type (p = 0.140), and diabetes (p = 0.198). On the other hand, old age (≥60 years) was related to delay in diagnosis (OR = 1.37; 95% CI = 1.12–1.68; p = 0.002). The chance of delay in diagnosis in prisoners was lower than in non-prisoners (OR = 0.62; 95% CI = 0.46–0.82; p = 0.001). CONCLUSIONS Old age was a risk factor for delay in diagnosis, and interestingly, prisoners had been diagnosed significantly faster.